(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes methods for detecting face masks in access control and management systems, and also presents a method of convolution neural networks for detecting face masks using deep machine learning technology. Face mask images in the form of a neural network model were trained on the generated database, and performance metrics were determined using metrics such as model accuracy, F1-score, precision and recall.